Extracellular matrix collagen biomarker levels in patients who underwent pulmonary endarterectomy - OLGUN YILDIZELİ, ŞEHNAZ; MUTLU, BÜLENT; YILDIZELİ, BEDRETTİN (My University, 2023)
OBJECTIVES: The role of extracellular matrix collagen biomarkers in chronic thromboembolic pulmonary hypertension (CTEPH) is not well known. Our goal was to investigate the matrix metalloproteinase (MMP)-2 and -9 protein levels in patients with CTETH.
Keywords: Tıp; Dahili Tıp Bilimleri; Göğüs Hastalıkları ve Allerji; Kardiyoloji; Cerrahi Tıp Bilimleri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Chest Diseases and Allergy; Cardiovascular; Surgery Medicine Sciences; Health Sciences; KALP VE KALP DAMAR SİSTEMLERİ; Klinik Tıp; Klinik Tıp (MED); SOLUNUM SİSTEMİ; CERRAHİ; CARDIAC & CARDIOVASCULAR SYSTEMS; CLINICAL MEDICINE; Clinical Medicine (MED); RESPIRATORY SYSTEM; SURGERY; Solunum Bakımı; Cerrahi; Akciğer ve Solunum Tıbbı; Kardiyoloji ve Kardiyovasküler Tıp; Respiratory Care; Surgery; Pulmonary and Respiratory Medicine; Cardiology and Cardiovascular Medicine; chronic thromboembolic pulmonary hypertension; pulmonary endarterectomy; matrix metalloproteinases 2 and 9; METALLOPROTEINASES; HYPERTENSION; TIMP-1